2001
DOI: 10.1002/gcc.1173
|View full text |Cite
|
Sign up to set email alerts
|

Loss of chromosome arms 3p and 9p and inactivation of P16INK4a in normal epithelium of patients with primary lung cancer

Abstract: The accumulation of genetic alterations in the respiratory epithelium may give rise to cancer and often is accompanied by a series of histologic alterations over a period of several years. Recent studies have identified some molecular alterations in histologically normal-appearing epithelium among patients with lung cancer. To extend these observations, we investigated clonal genetic alterations by using fluorescence in situ hybridization (FISH) analysis and immunohistochemistry in 69 biopsy samples of histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(27 reference statements)
0
13
0
2
Order By: Relevance
“…Genetic alterations involving the 9p21 region are common in human cancers and the p16 gene is considered to be a target in this region . This gene, in fact, can be inactivated by different mechanisms, most of which lead to the complete absence of the protein, for example, homozygous deletion, loss of heterozygosity (LOH), methylation of the promoter region, point mutations (generally nonsense) and frameshift, with an extremely variable incidence according to the type of tumor Herman et al, 1995;Jares et al, 1999;Caballero et al, 2001). Homozygous deletions of large fragments which eliminate the INK4a locus frequently occur in bladder, breast, and prostate carcinomas, glioblastomas, mesotheliomas (Cheng et al, 1994;Cairns et al, 1995;Balazs et al, 1997;Stadler et al, 2001).…”
Section: The P16mentioning
confidence: 99%
“…Genetic alterations involving the 9p21 region are common in human cancers and the p16 gene is considered to be a target in this region . This gene, in fact, can be inactivated by different mechanisms, most of which lead to the complete absence of the protein, for example, homozygous deletion, loss of heterozygosity (LOH), methylation of the promoter region, point mutations (generally nonsense) and frameshift, with an extremely variable incidence according to the type of tumor Herman et al, 1995;Jares et al, 1999;Caballero et al, 2001). Homozygous deletions of large fragments which eliminate the INK4a locus frequently occur in bladder, breast, and prostate carcinomas, glioblastomas, mesotheliomas (Cheng et al, 1994;Cairns et al, 1995;Balazs et al, 1997;Stadler et al, 2001).…”
Section: The P16mentioning
confidence: 99%
“…In recent studies, loss of one allele of chromosomes 3p, 9p, and 17p was observed in normal bronchial mucosa at different locations of current and former smokers. [4][5][6][7][8] Similarly, the mutation TP53 has been detected in the histologically normal lung tissue of lung cancer patients. 9 Conversely, loss-of-heterozygosity analysis of multiple sites from a number of patients failed to show a common clonal change in such lesions, an observation that would be consistent with independence of origin.…”
mentioning
confidence: 99%
“…In addition, chromosome 9 aberrations in normal bronchial epithelium or in normal lung tissue of lung cancer patients have been observed by several investigators. 14,23 Moreover, chromosomal instability in lymphocytes has been recently shown to be associated with oral premalignant lesions. 24 These studies suggest that the presence of chromosome 9 aberrations in lymphocytes (nontarget tissue) might represent the cause and not a consequence of the disease.…”
Section: Discussionmentioning
confidence: 99%